A Child with HIV (Human Immunodeficiency Virus) Infection Accompanied by Severe Acute Malnutrition: A Case Report - Darma, Sidrah; Nawing, Herry D.; Meutia Pelupessy, Ninny; Albar, Husein (Fakultas Kedokteran Universitas Muslim Indonesia, 2020)
Joint United Nations Programme in HIV/AIDS (UNAIDS) reported that 1.8 million children under 15 years old had HIV with 150,000 new pediatric cases in 2015, and only 49% had an antiretroviral (ARV) therapy. Mortality in HIV-infected children with severe acute malnutrition was 30.4% in Africa. A 1-year and 8-months-old girl was hospitalized due to diarrhea, vomiting, oral thrush, and recurrent fever before admission. She has been hospitalized for HIV infection one month ago and treated with ARV. Her mother was treated with ARV before. Physical examination showed a severely ill, poorly nourished, stunting, and conscious child with normal vital signs. There was oral thrush. The evidence of nutritional marasmus was old man face, piano sign, wasting, and baggy pants. Laboratory findings revealed anemia, positive antigen and antibody of HIV infection, and low Cluster of Differentiation 4 (CD4). She was treated with ARV, Cotrimoxazole, and management of malnutrition and diarrhea. The prognosis of the patient was poor. A 1-year and 8-months-old girl with HIV infection complicated with severe acute malnutrition, acute diarrhea, oral thrush, and anemia of chronic disease were reported. The diagnosis was based on clinical and laboratory findings. Management focused on the therapy of HIV and accompanying illness. The prognosis was poor.